In vitro degradation behavior of novel Zn–Cu–Li alloys: Roles of alloy composition and rolling processing - Shiyu Huang (Elsevier, 2021)
Zn–alloys are considered to be promising biodegradable materials due to suitable degradation rates. In this paper, novel Zn–Cu–Li alloys with layered CuZn4 structure were achieved. The corrosion properties of newly developed biodegradable Zn–Cu–Li alloys in simulated body fluid was studied. Results indicated that the cold-rolled alloys presented a relatively uniform corrosion mode, although early corrosion occurred preferentially at phase boundaries. Galvanic corrosion and corrosion product films jointly determined the later corrosion process. Cu improved the corrosion potential and film properties in its solid solution state, induced galvanic corrosion, and provided a physical barrier to corrosion by forming CuZn4 phase. Rolling accelerated the initial corrosion rate by enhancing the matrix electrochemical activity, while it contributed to uniform corrosion by improving the CuZn4 phase shape. Finally, cold-rolled Zn–4Cu–0.02Li possessed the best corrosion resistance and mechanical properties combination among the prepared alloys, with a yield strength of 256 MPa, an ultimate strength of 342 MPa, a fracture elongation of 39.8 %, and a corrosion rate of nearly 55 μm/year.